The Role Of Compensation Systems In Enhancing Employee Loyalty: A Case Study Of UD Erwin - Erwin Syah Putra Gulo; Meiman Hidayat Waruwu (UNIVED Press, 2025)
This study aims provides practical recommendations on aligning compensation strategies with corporate values and adapting them to meet the evolving needs of the workforce. This is especially relevant for organizations like UD Erwin, which are looking to create a sustainable, motivated, and loyal workforce. The paper's focus on both financial and non-financial aspects of employee well-being makes it particularly valuable for managers, HR professionals, and organizational leaders who want to enhance employee engagement, ensure job satisfaction, and ultimately improve organizational performance. The findings offer actionable insights that can be implemented in real-world business contexts, helping organizations build stronger relationships with employees, adapt to changing economic conditions, and thrive in a competitive environment. The future success of UD Erwin hinges on its ability to adapt its compensation strategies and organizational culture to the evolving needs of its workforce. By valuing both financial and non-financial aspects of employee well-being, UD Erwin can foster sustained loyalty, enhance employee engagement, and drive improved performance, ensuring long-term organizational success